Human neutrophil collagenase cleaves α1-antitrypsin - J Michaelis; Margreet C.M. Vissers; C C Winterbourn (1990)
Inactivation of the plasma serine-proteinase inhibitor alpha 1-antitrypsin (alpha 1-AT) by neutrophil metalloproteinases has been reported [Vissers, George, Bathurst, Brennan & Winterbourn (1987) Fed. Proc. Fed. Am. Soc. Exp. Biol. 46, 1390a; (1988) J. Clin. Invest. 82, 706-711; Desrochers & Weiss (1988) J. Clin. Invest. 81, 1646-1650]. To identify the enzyme responsible, supernatant from neutrophils stimulated with phorbol 12-myristate 13-acetate was subjected to preparative SDS/PAGE, both with and without activation of latent metalloproteinases with HgCl2. The lanes were subsequently sliced into pieces, the slices incubated with equimolar amounts of type I collagen and alpha 1-AT in the presence of HgCl2, and the reaction products separated by SDS/PAGE. With the latent supernatant, the characteristic collagen-cleavage products and cleaved alpha 1-AT were present in the same slices, corresponding to an Mr of 80,000-85,000. On treatment with HgCl2 both degradative activities underwent the same molecular-mass shift to a position corresponding to Mr 60,000-65,000. Western blots of neutrophil supernatants, using a polyclonal antibody to purified collagenase, showed Mr values of 83,000 for the latent enzyme and 63,000 for the HgCl2-activated enzyme. Neutrophil collagenase was purified to homogeneity and shown also to exist in a second latent form with Mr 70,000. When activated to the Mr-63,000 form by HgCl2 and incubated with equimolar amounts of collagen and alpha 1-AT, collagenase cleaved alpha 1-AT at almost twice the rate at which collagen was cleaved. alpha 1-AT cleavage was inhibited by 1,10-phenanthroline and by high concentrations of collagen. That the purified collagenase did not contain a contaminant proteinase such as stromelysin was indicated by inability of the preparation to cleave casein. Taken together these results lead us to conclude that neutrophil collagenase is capable of degrading alpha 1-AT. Neutrophil gelatinase also cleaved alpha 1-AT, but cleavage was slow when compared with its activity against gelatin.